Karakterisasi keragaman dan analisis kekerabatan berdasarkan sifat agronomi jagung berwarna (Zea mays L.) - Firda Lailatus Sa’adah; Florentina Kusmiyati; Syaiful Anwar (Universitas Lancang Kuning, 2022)
Maize has a wide diversity. The diversity of maize exceeds that of any other species and is used and conserved by traditional maize farmers. The way to find information about maize diversity is to evaluate the maize genotype through plant characterization. Plant characteristics include observing the qualitative and quantitative traits to identify and select appropriate parental species for use in forming or developing varieties. This study aimed to examine the diversity of agronomic traits in 12 genotypes of colored maize; Meanwhile, Bonanza (sweet maize) was used as a control. An augmented design with the basic design of a completely randomized design was used as a research experiment. From the agronomic data, cluster analysis between characters was carried out based on the Euclidean distance coefficient using the MVSP application to determine the relationship between genotypes. The observations of quantitative and qualitative traits showed that the characteristics of plant height, seed color, stem color, tassel color, and cob hair had heterogeneous diversity. However, sweetness, cob color, seed type, and seed row arrangement had homogeneous diversity in the male and female flowering age characters. Based on the dendrogram results, the twelve genotypes tested and the control showed that these genotypes were different varieties in one genus, i.e., Zea L. because they had a similarity value above 80%.